RADIO AND MARKETING PUBLIC RELATIONS - Prayoga, Deohan Arustama (Paradigma: Jurnal Masalah Sosial, Politik, dan Kebijakan, 2018)
Abstract Radio that until now is still in use and practical for the public as a medium of information but now it is used as a media Promotion Marketing Public Relations. Marketing Public Relations serves to provide understanding to the public about the company's products. In realizing Marketing Public Relations strategy through events that have been programmed PT TWCBP & RB using Radio TWC as Marketing Public Relation. Radio TWC is required to provide innovation in promotional activities. The research method used case study research where the researcher describes the object of research based on facts that exist and correlated with Social Interaction theory which social process can be done and progressed through action and interaction. Techniques of collecting data using interviews, observation, documentation and literature study. The results showed that Radio TWC conducted various activities with the public as an effort to provide information, build trust, and interest to the Taman Wisata Candi through the publication of events and promotions. So from the activities of Marketing Public Relation Radio TWC is considered effective to run the role as a medium to provide information to the public company and the source of evaluation to the company about the activities of Marketing Public Relations.